2022
DOI: 10.1007/s10346-022-01948-x
|View full text |Cite
|
Sign up to set email alerts
|

Realistic visualization of debris flow type landslides through virtual reality

Abstract: Immersive media technologies, such as virtual and augmented reality, have recently enabled a more holistic way to comprehend natural hazards. In this work, we aim at visualizing the temporal and spatial evolution of a debris flow in a virtual reality environment. We develop a framework to integrate the output results obtained from a debris flow numerical model into virtual reality. To guide the framework, a real debris flow event, which happened in Hunnedalen (Norway) in 2016 and blocked a road network, is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These coordinates and their interpolated velocities were exported into Unity using customized C# script. The details of the procedure is outlined in (Alene et al 2022a) and (Alene et al 2022b). The details of the numerical simulation and preprocessing of the simulation results were given in supplementary information, SI1(online resource).…”
Section: Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These coordinates and their interpolated velocities were exported into Unity using customized C# script. The details of the procedure is outlined in (Alene et al 2022a) and (Alene et al 2022b). The details of the numerical simulation and preprocessing of the simulation results were given in supplementary information, SI1(online resource).…”
Section: Physicsmentioning
confidence: 99%
“…It was provided as a DTM. A custom script based on Unity C#(C-sharp) was used to import the DTM into Unity using the method mentioned in (Alene et al 2022b). This allowed us to show the actual location and orientation of natural features of topography such as rivers and slopes.…”
Section: Virtual Environment Representationmentioning
confidence: 99%
“…Both domestic and international scholars have divided the effective time period of antecedent rainfall into 4 days, 10 days, 15 days, and 18 days. It has been found that the correlation between the 15-day antecedent effective rainfall and landslide disasters is the highest (Alene et al 2023). Since this study focuses on underground debris flows in mines, which exhibit a delayed effect in terms of occurrence, various factors were considered.…”
Section: Effective Rainfall Modelmentioning
confidence: 99%
“…Another strand of methods combines the simple two-dimensional landslide model with the experimental test, and then constructs the three-dimensional prediction visual model. For example, researchers [19] obtained two-dimensional simulation results of a landslide area, the dip angle and influence depth based on a two-dimensional map of landslide monitoring. Other researchers [20] combined field monitoring with experimental tests and established a three-dimensional visualization model of landslide form prediction.…”
Section: Landslide Visualizationmentioning
confidence: 99%